Research on the Operational Efficiency of Basic Medical Insurance for Urban Employees in China–Based on Three-Stage DEA Model - Peng N; Guo H; Wu Y; Liu P (Dove Medical Press, 2023)
Nan Peng,* Hanyang Guo,* You Wu, Pengcheng Liu School of International Pharmaceutical Business, China Pharmaceutical University, Nanjing, Jiangsu, People's Republic of China*These authors contributed equally to this workCorrespondence: Pengcheng Liu, School of International Pharmaceutical Business, China Pharmaceutical University, Nanjing, Jiangsu, People's Republic of China, Tel +86 13851619607, Email liupcmail@163.comPurpose: To conduct a three-stage data envelopment analysis (DEA) of the operational efficiency of urban employee basic medical insurance (UEBMI) across 31 provinces in China from 2012 to 2021.Methods: Utilized a three-stage DEA model, this study measured and evaluated the operational efficiency of urban employee basic medical insurance within China's 31 provinces.Results: The operational efficiency of urban employee basic medical insurance in China was notably low, displaying significant disparities across different regions and periods. Substantial room for improvement exists. Environmental factors, including urbanization level and unemployment rate, wielded a pronounced influence on the operational efficiency of China's employee medical insurance. Conversely, the fiscal revenue and expenditure ratio hindered the enhancement of employee medical insurance efficiency.Conclusion: This study held valuable insights for enhancing the operational efficiency of China's urban employee basic medical insurance. To effectively improve insurance efficiency, the following recommendations are put forth: firstly, relevant departments should escalate resource investments and optimize resource utilization based on rational allocation; secondly, enhance legislation and regulations, fortify fund oversight, and ensure equitable and judicious utilization of the medical insurance fund; finally, leveraging modern high-tech advancements can comprehensively elevate the operational efficiency of the employee medical insurance fund. Ultimately, with the advent of cutting-edge technology, the operational efficiency of employee medical insurance fund can be comprehensively elevated.Keywords: three-stage DEA, urban employee basic medical insurance, medical insurance fund, operational efficiency, technical efficiency